Water Sorption and Desorption of Isolated Cuticles From Three Woody Species With Focus on Ilex aquifolium - Vega, Clara; Valbuena-Carabaña, María; Gil, Luis; Fernández, Victoria (Frontiers in Plant Science, 2021)
The cuticle is a lipid-rich layer that protects aerial plant organs against multiple stress factors such as dehydration. In this study, cuticle composition and structure in relation to water loss are examined in a broad ecophysiological context, taking into consideration leaf age and side from Ilex aquifolium (holly) in comparison with Eucalyptus globulus (eucalypt) and Prunus laurocerasus (cherry laurel). Enzymatically isolated cuticular membranes from holly leaves were studied under three treatment conditions: natural (no chemical treatment), after dewaxing, and after methanolysis, and the rate of water loss was assessed. Structural and chemical changes were evaluated using different microscopy techniques and by Fourier transform infrared (FTIR) spectroscopy. The potential mechanisms of solute absorption by holly leaves were additionally evaluated, also testing if its prickly leaf margin may facilitate uptake. The results indicate that the treatment conditions led to structural changes, and that chemical composition was hardly affected because of the occurrence of cutan. Structural changes led to more hydrophilic adaxial surfaces, which retained more water and were more efficient than natural cuticles, while changes were not significant for abaxial surfaces. Across natural cuticles, age was a significant factor for eucalypt but not for holly. Young eucalypt cuticles were the group that absorbed more water and had the lowest water loss rate. When comparing older leaf cuticles of the three species, cherry laurel was found to absorb more water, which was, however, lost more slowly, compared with the other species. Evidence was gained that holly leaves can absorb foliar-applied solutes (traced after calcium chloride application) through the adaxial and abaxial surfaces, the adaxial mid veins, and to a lower extent, the spines. In conclusion, for the species examined, the results show variations in leaf cuticle composition and structure in relation to leaf ontogeny, and water sorption and desorption capacity.